Arabic educational vocabulary games for beginners - Sahrir, Muhammad Sabri; Md Ghalib, Mohd. Feham (2015)

(untitled)
Educational game or Digital Game-based Learning (DGBL) has been among teaching and learning aids in many disciplines of knowledge. This project presents a an educational product of Arabic educational games for beginners that was specifically designed for pre-university students of Non-Arabic native speakers at the Centre for Foundation Studies (CFS), International Islamic University Malaysia (IIUM). This educational games in Arabic vocabulary are being used by the learners since 2011 until now. This digital games prototype is using web-based platform with Raptivity e-authoring tool in the prototype development process with a conpendium of 34 various language games for Arabic language learners.